Analysis Of The Readiness Of Medical Record Officers In The Outpatient Unit To The Use Of RME By TRI Methods At RSUD Dr. M. Ashari Pemalang - Navisa Putri, Mayliana; Setiono, Oki; Astuti S., Retno; Widianawati, Evina (Health Science UDINUS, 2024)
The readiness of medical record officers in the Electronic Medical Records (EMR) should follow Permenkes Number 24 of 2022 Article 45. RSUD Dr. M. Ashari Pemalang has just implemented EMR, so it was necessary to measure the readiness of medical record officers in the outpatient department using the TRI (Technology Readiness Index) method. This research method is descriptive quantitative. The data collection technique used was a questionnaire. The sampling technique in this study used a total sampling technique; the research subjects were all medical record officers in the Outpatient Department of RSUD, Dr. M. Ashari Pemalang (26 officers). The results showed that the average readiness score of medical record officers in the outpatient department of RSUD Dr. M. Ashari Pemalang, based on the dimensions of optimism, innovation, insecurity, and discomfort, was 31.42, 27.81, 23.81, and 22.54, respectively. According to the four dimensions of TRI, the readiness level to use EMR among most medical record officers of the outpatient department was classified as Ready (73% of officers). However, training and mentoring for the relevant officers is still necessary to optimize the use of the new technology.